Solid electrolyte membrane applied to solid battery
By using polypropylene resin, modified graphene and iron p-toluenesulfonate, the problems of low conductivity of solid polymer electrolyte and leakage of liquid electrolyte are solved, and the mechanical and electrical properties optimization of the electrolyte membrane of solid state battery is achieved.
Patent Information
- Application Number
- CN202510022014.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
The existing solid polymer electrolytes have low ionic conductivity and there is a risk of leakage after doping with liquid electrolytes, which affects safety.
A solid electrolyte film with polypropylene resin, modified graphene and iron p-toluenesulfonate as the main components was prepared by ultrasonic dispersion and rotary distillation, and combined with HCl gas etching, a film with excellent mechanical and electrical properties was obtained.
The high tensile strength and high ionic conductivity of the solid electrolyte membrane in solid-state batteries are achieved, ensuring the optimization of the mechanical and electrical properties of the membrane, while avoiding the risk of leakage of liquid electrolytes.
Smart Images

Figure BDA0005231656340000041 
Figure BDA0005231656340000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid batteries, and in particular to a solid electrolyte membrane applied to solid batteries. Background Art
[0002] Solid-state batteries are batteries that use solid electrodes and solid electrolytes. Compared with the widely used organic electrolyte lithium-ion batteries, solid-state batteries do not contain liquid electrolytes, thus avoiding the occurrence of leakage and other problems, making solid-state batteries safer. In addition, the core advantage of solid-state batteries lies in their high energy density, which can theoretically reach 400Wh / kg. Moreover, solid-state batteries are stable under high temperature conditions, are not prone to thermal runaway, and the risk of spontaneous combustion and explosion is greatly reduced. Therefore, solid-state batteries have become an ideal object for the next generation of new energy vehicle power batteries.
[0003] Existing solid electrolytes are mainly divided into three categories, namely polymer solid electrolytes, sulfide solid electrolytes and oxide solid electrolytes. Among them, polymer solid electrolytes are composed of a polymer matrix (such as polyester, polyenzyme or polyamine) and a lithium salt (such as LiClO4, LiAsF4, LiPF6 or LiBF4); however, since ion transport in solid polymer electrolytes mainly occurs in the amorphous region and the polymer matrix has a high degree of crystallinity, the ionic conductivity of the polymer solid electrolyte is relatively low.
[0004] In order to improve the ionic conductivity of polymer solid electrolytes, some studies have been conducted on doping certain liquid electrolytes into polymer solid electrolytes. However, although this method can effectively improve the ionic conductivity of polymer solid electrolytes, the doping of liquid electrolytes greatly increases the risk of liquid electrolyte leakage, which is not conducive to the safety of polymer solid electrolytes. Based on this, in order to prevent the leakage of liquid electrolytes doped in solid electrolytes, providing a solid electrolyte membrane with high mechanical and electrical properties has become a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0005] The purpose of the present invention is to provide a solid electrolyte membrane for use in solid batteries, wherein the solid electrolyte membrane has excellent mechanical and electrical properties.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A solid electrolyte membrane for solid batteries, comprising the following raw materials in parts by weight:
[0009] 4-6 parts of polypropylene resin, 0.5-1.5 parts of modified graphene and 0.1-0.5 parts of iron p-toluenesulfonate.
[0010] Furthermore, the method for preparing the modified graphene comprises the following steps:
[0011] 1) adding phosphoric acid and thiourea to a graphene solution, ultrasonically dispersing, reacting, washing, and drying to obtain phosphorus-sulfur co-doped graphene;
[0012] 2) The phosphorus-sulfur co-doped graphene obtained in step 1), silicon dioxide and lithium difluorooxalate borate are mixed, ball-milled and calcined to obtain the modified graphene.
[0013] Furthermore, in step 1), the concentration of the graphene solution is 1 g / L.
[0014] Furthermore, in step 1), the mass volume ratio of the phosphoric acid, thiourea and graphene solution is (1-2) g: (0.5-1.5) g: 5 mL.
[0015] Furthermore, in step 1), the duration of the ultrasonic dispersion is 1 to 2 hours.
[0016] Furthermore, in step 1), the reaction is specifically: reacting at 150° C. for 6 to 8 hours.
[0017] Furthermore, in step 2), the mass ratio of the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalatoborate is 10g:(1-3)g:(0.5-1.5)g.
[0018] Furthermore, in step 2), the ball milling time is 30 minutes.
[0019] Furthermore, in step 2), the calcination is specifically: calcining at 200° C. for 30 to 60 minutes.
[0020] The second technical solution of the present invention:
[0021] The method for preparing the solid electrolyte membrane for solid batteries comprises the following steps:
[0022] 1) adding polypropylene resin, modified graphene and iron p-toluenesulfonate into cyclohexane, and ultrasonically dispersing the mixture to obtain a polypropylene mixed solution;
[0023] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating the mixture to obtain a solid electrolyte membrane precursor;
[0024] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an HCl gas atmosphere and etching it to obtain the solid electrolyte membrane.
[0025] Furthermore, in step 1), the mass volume ratio of the polypropylene resin, modified graphene, iron p-toluenesulfonate and cyclohexane is (4-6) g: (0.5-1.5) g: (0.1-0.5) g: 10 mL.
[0026] Furthermore, in step 1), the duration of the ultrasonic dispersion is 30 minutes.
[0027] Furthermore, in step 2), the rotary evaporation is specifically: rotary evaporation at 130-160° C. for 20 min.
[0028] Furthermore, in step 2), the thickness of the solid electrolyte membrane precursor is 0.5 to 1 mm.
[0029] Furthermore, in step 3), the HCl gas atmosphere is specifically: an HCl gas atmosphere with a volume fraction of 15%.
[0030] Furthermore, in step 3), the etching is specifically: etching at 60° C. for 10 to 20 minutes.
[0031] The third technical solution of the present invention:
[0032] The above-mentioned solid electrolyte membrane for solid batteries is used in solid-state batteries.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The solid electrolyte membrane used in solid batteries provided by the present invention has a tensile strength of up to 9.5 MPa and an ionic conductivity of up to 4.6×10 -4 S cm -1 , with excellent mechanical and electrical properties. DETAILED DESCRIPTION
[0035] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0036] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] In the following examples and comparative examples, unless otherwise specified, all raw materials used are commercially available, some of which can be found in Table 1;
[0041] Table 1 Raw materials and purchase channels
[0042]
[0043] In the following embodiments, a method for preparing a solid electrolyte membrane for a solid battery comprises the following steps:
[0044] 1. Preparation of modified graphene:
[0045] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of (1-2) g: (0.5-1.5) g: 5 mL, ultrasonically dispersing for 1-2 h, reacting at 150° C. for 6-8 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0046] 2) mixing the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: (1-3) g: (0.5-1.5) g, ball milling for 30 min, and then calcining at 200° C. for 30-60 min to obtain modified graphene;
[0047] 2. Preparation of solid electrolyte membrane:
[0048] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of (4-6) g: (0.5-1.5) g: (0.1-0.5) g: 10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0049] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 130-160° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.5-1 mm;
[0050] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 10 to 20 minutes to obtain the solid electrolyte membrane.
[0051] Example 1
[0052] A solid electrolyte membrane for solid batteries
[0053] 1. Preparation of modified graphene:
[0054] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 1 g:0.5 g:5 mL, ultrasonically dispersing for 1 h, then reacting at 150° C. for 6 h, washing, and drying to obtain phosphorus-sulfur co-doped graphene;
[0055] 2) mixing the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of 10 g: 1 g: 0.5 g, ball milling for 30 min, and then calcining at 200° C. for 30 min to obtain modified graphene;
[0056] 2. Preparation of solid electrolyte membrane:
[0057] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 4 g: 0.5 g: 0.1 g: 10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0058] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 130° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.5 mm;
[0059] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 10 min to obtain the solid electrolyte membrane.
[0060] Example 2
[0061] A solid electrolyte membrane for solid batteries
[0062] 1. Preparation of modified graphene:
[0063] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 1.5 g:1 g:5 mL, ultrasonically dispersing for 1.5 h, then reacting at 150° C. for 7 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0064] 2) mixing the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: 2 g: 1 g, ball milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0065] 2. Preparation of solid electrolyte membrane:
[0066] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0067] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0068] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0069] Example 3
[0070] A solid electrolyte membrane for solid batteries
[0071] 1. Preparation of modified graphene:
[0072] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 2 g:1.5 g:5 mL, ultrasonically dispersing for 2 h, then reacting at 150° C. for 8 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0073] 2) mixing the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g:3 g:1.5 g, ball milling for 30 min, and then calcining at 200° C. for 60 min to obtain modified graphene;
[0074] 2. Preparation of solid electrolyte membrane:
[0075] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 6 g:1.5 g:0.5 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0076] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 160° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 1 mm;
[0077] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 20 minutes to obtain the solid electrolyte membrane.
[0078] Comparative Example 1
[0079] A solid electrolyte membrane for solid batteries
[0080] 1. Preparation of modified graphene:
[0081] 1) adding phosphoric acid to a graphene solution having a concentration of 1 g / L according to a mass volume ratio of phosphoric acid to graphene solution of 1.5 g:5 mL, ultrasonically dispersing for 1.5 h, reacting at 150° C. for 7 h, washing, and drying to obtain phosphorus-doped graphene;
[0082] 2) mixing the phosphorus-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of phosphorus-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: 2 g: 1 g, ball-milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0083] 2. Preparation of solid electrolyte membrane:
[0084] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0085] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0086] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0087] Comparative Example 2
[0088] A solid electrolyte membrane for solid batteries
[0089] 1. Preparation of modified graphene:
[0090] 1) adding thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of thiourea to graphene solution of 1 g:5 mL, ultrasonically dispersing for 1.5 h, then reacting at 150° C. for 7 h, washing, and drying to obtain sulfur-doped graphene;
[0091] 2) mixing the sulfur-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of sulfur-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: 2 g: 1 g, ball milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0092] 2. Preparation of solid electrolyte membrane:
[0093] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0094] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0095] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0096] Comparative Example 3
[0097] A solid electrolyte membrane for solid batteries
[0098] 1. Preparation of modified graphene:
[0099] 1) According to the mass ratio of graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: 2 g: 1 g, graphene, silicon dioxide and lithium difluorooxalate borate are mixed, ball milled for 30 min, and then calcined at 200 ° C. for 40 min to obtain modified graphene;
[0100] 2. Preparation of solid electrolyte membrane:
[0101] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0102] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0103] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0104] Comparative Example 4
[0105] A solid electrolyte membrane for solid batteries
[0106] 1. Preparation of modified graphene:
[0107] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 1.5 g:1 g:5 mL, ultrasonically dispersing for 1.5 h, then reacting at 150° C. for 7 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0108] 2) mixing the phosphorus-sulfur co-doped graphene and lithium difluorooxalate borate obtained in step 1) in a mass ratio of 10 g:1 g, ball milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0109] 2. Preparation of solid electrolyte membrane:
[0110] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0111] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0112] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0113] Comparative Example 5
[0114] A solid electrolyte membrane for solid batteries
[0115] 1. Preparation of modified graphene:
[0116] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 1.5 g:1 g:5 mL, ultrasonically dispersing for 1.5 h, then reacting at 150° C. for 7 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0117] 2) mixing the phosphorus-sulfur co-doped graphene and silicon dioxide obtained in step 1) in a mass ratio of phosphorus-sulfur co-doped graphene to silicon dioxide of 10 g:2 g, ball milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0118] 2. Preparation of solid electrolyte membrane:
[0119] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0120] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0121] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0122] Comparative Example 6
[0123] A solid electrolyte membrane for solid batteries
[0124] 1. Preparation of modified graphene:
[0125] According to the mass volume ratio of phosphoric acid, thiourea and graphene solution of 1.5g:1g:5mL, phosphoric acid and thiourea were added to the graphene solution with a concentration of 1g / L, ultrasonically dispersed for 1.5h, then reacted at 150°C for 7h, washed and dried to obtain phosphorus-sulfur co-doped graphene, i.e. modified graphene;
[0126] 2. Preparation of solid electrolyte membrane:
[0127] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0128] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0129] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0130] Comparative Example 7
[0131] A solid electrolyte membrane for solid batteries
[0132] 1) adding polypropylene resin, graphene and iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0133] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0134] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0135] Comparative Example 8
[0136] A solid electrolyte membrane for solid batteries
[0137] 1) adding polypropylene resin and ferric p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:0.3 g:10 mL, and ultrasonically dispersing for 30 minutes to obtain a polypropylene mixed solution;
[0138] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0139] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0140] Comparative Example 9
[0141] A solid electrolyte membrane for solid batteries
[0142] 1. Preparation of modified graphene:
[0143] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 1.5 g:1 g:5 mL, ultrasonically dispersing for 1.5 h, then reacting at 150° C. for 7 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0144] 2) mixing the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: 2 g: 1 g, ball milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0145] 2. Preparation of solid electrolyte membrane:
[0146] 1) adding the polypropylene resin and the modified graphene prepared in step 1 to cyclohexane in a mass volume ratio of 5 g:1 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0147] 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating at 140° C. for 20 min to obtain a solid electrolyte membrane precursor with a thickness of 0.7 mm;
[0148] 3) placing the solid electrolyte membrane precursor obtained in step 2) in an atmosphere of 15% by volume HCl gas, and etching at 60° C. for 15 minutes to obtain the solid electrolyte membrane.
[0149] Comparative Example 10
[0150] A solid electrolyte membrane for solid batteries
[0151] 1. Preparation of modified graphene:
[0152] 1) adding phosphoric acid and thiourea to a graphene solution with a concentration of 1 g / L according to a mass volume ratio of phosphoric acid, thiourea and graphene solution of 1.5 g:1 g:5 mL, ultrasonically dispersing for 1.5 h, then reacting at 150° C. for 7 h, washing and drying to obtain phosphorus-sulfur co-doped graphene;
[0153] 2) mixing the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate obtained in step 1) in a mass ratio of phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalate borate of 10 g: 2 g: 1 g, ball milling for 30 min, and then calcining at 200° C. for 40 min to obtain modified graphene;
[0154] 2. Preparation of solid electrolyte membrane:
[0155] 1) adding the polypropylene resin, the modified graphene prepared in step 1 and the iron p-toluenesulfonate to cyclohexane in a mass volume ratio of 5 g:1 g:0.3 g:10 mL, and ultrasonically dispersing for 30 min to obtain a polypropylene mixed solution;
[0156] 2) The polypropylene mixed solution obtained in step 1) was cast into a flat mold and rotary evaporated at 140° C. for 20 min to obtain a solid electrolyte membrane with a thickness of 0.7 mm.
[0157] The mechanical and electrical properties of the solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 10 were tested. The results of the mechanical and electrical properties tests are shown in Table 2.
[0158] Table 2 Mechanical and electrical properties test results
[0159]
[0160] From the data in Table 2, it can be seen that the tensile strength of the solid electrolyte membrane used in solid batteries provided by the present invention can reach 9.5 MPa, and the ionic conductivity can reach 4.6×10 -4 S cm -1 , with better mechanical and electrical properties; however, omitting any step or any raw material in the preparation process of modified graphene, preparing the solid electrolyte membrane with graphene as the raw material, omitting the addition of modified graphene or iron p-toluenesulfonate, and omitting the sintering of the solid electrolyte membrane precursor will reduce the mechanical and electrical properties of the solid electrolyte membrane to a certain extent.
[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A solid electrolyte membrane for solid batteries, characterized in that: Including the following raw materials by weight: 4-6 parts of polypropylene resin, 0.5-1.5 parts of modified graphene and 0.1-0.5 parts of iron p-toluenesulfonate.
2. A solid electrolyte membrane for solid batteries according to claim 1, characterized in that: The preparation method of the modified graphene comprises the following steps: 1) adding phosphoric acid and thiourea to a graphene solution, ultrasonically dispersing, reacting, washing, and drying to obtain phosphorus-sulfur co-doped graphene; 2) The phosphorus-sulfur co-doped graphene obtained in step 1), silicon dioxide and lithium difluorooxalate borate are mixed, ball-milled and calcined to obtain the modified graphene.
3. A solid electrolyte membrane for solid batteries according to claim 2, characterized in that: In step 1), the concentration of the graphene solution is 1 g / L; the mass volume ratio of the phosphoric acid, thiourea and graphene solution is (1-2) g: (0.5-1.5) g: 5 mL; the duration of the ultrasonic dispersion is 1-2 h; and the reaction is specifically: reacting at 150° C. for 6-8 h.
4. The solid electrolyte membrane for solid batteries according to claim 2, characterized in that: In step 2), the mass ratio of the phosphorus-sulfur co-doped graphene, silicon dioxide and lithium difluorooxalatoborate is 10g:(1-3)g:(0.5-1.5)g; the ball milling time is 30min; and the calcination is specifically: calcining at 200°C for 30-60min.
5. A method for preparing a solid electrolyte membrane for a solid battery as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: 1) adding polypropylene resin, modified graphene and iron p-toluenesulfonate into cyclohexane, and ultrasonically dispersing the mixture to obtain a polypropylene mixed solution; 2) casting the polypropylene mixed solution obtained in step 1) into a flat mold, and rotary evaporating the mixture to obtain a solid electrolyte membrane precursor; 3) placing the solid electrolyte membrane precursor obtained in step 2) in an HCl gas atmosphere and etching it to obtain the solid electrolyte membrane.
6. The preparation method according to claim 5, characterized in that: In step 1), the mass volume ratio of the polypropylene resin, modified graphene, iron p-toluenesulfonate and cyclohexane is (4-6) g: (0.5-1.5) g: (0.1-0.5) g: 10 mL; and the duration of the ultrasonic dispersion is 30 min.
7. The preparation method according to claim 5, characterized in that: In step 2), the rotary evaporation is specifically: rotary evaporation at 130-160° C. for 20 min; the thickness of the solid electrolyte membrane precursor is 0.5-1 mm.
8. The preparation method according to claim 5, characterized in that: In step 3), the HCl gas atmosphere is specifically: an HCl gas atmosphere with a volume fraction of 15%; in step 3), the etching is specifically: etching at 60° C. for 10 to 20 minutes.
9. Use of the solid electrolyte membrane for solid batteries as claimed in any one of claims 1 to 4 in solid-state batteries.